Integrating Hands-on and Virtual Learning for Environmental Sustainability: Eco Enzyme Soap Making at Stella Matutina - Dwi Putranti, Honorata Ratnawati; Danang, Danang; Brito Da Silva, Teodora Maria Fernandes; B Pujiati, Agnes Agnesita (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2025)
This Community Service Program aimed to implement and evaluate an Experimental Hybrid Learning Model at SMP Stela Martutina, Salatiga, Central Java. The program focused on enhancing students' conceptual understanding and practical skills by integrating concrete and virtual experiences in eco enzyme soap making. The program led to a significant increase in students' knowledge of environmental issues and their practical abilities in eco enzyme production. Moreover, students showed improved engagement in both physical and virtual learning environments. This hybrid learning approach proved effective in achieving educational goals and holds potential for broader implementation in other educational contexts.